Theoretical Study of the Addition Reaction of Arylazides to 1,3-Dicarbonyl Compounds - Adda Abdelghani; Halima Hadj Mokhtar; Ouda Boumaza; Abderrahmane Naous (Chemistry Proceedings, 2023)
Our research focuses on the synthesis of 1,2,3-triazoles through 1,3-dipolar cycloaddition involving arylazides. The reaction demonstrates high efficiency when conducted in the presence of morpholine, resulting in 100% regioselectivity towards a single isomer. A theoretical study of this reaction can be conducted to gain insights into its mechanism and provide valuable information for its optimization. This study involves the use of computational methods, such as density functional theory (DFT), to calculate the structures, energies, and properties of the reactants, intermediates, transition states, and products involved in the reaction. The calculations were performed using the Gaussian09 program with the B3LYP(GD3BJ)/6-31G(d,p) method.